2015
DOI: 10.1890/es14-00361.1
|View full text |Cite
|
Sign up to set email alerts
|

Historical data reveal fish assemblage shifts in an unregulated prairie river

Abstract: Wyoming's Powder River is considered an example of a pristine prairie river system. While the river hosts a largely native fish assemblage and remains unimpounded over its 1,146‐km course to the Yellowstone River confluence, the hydrologic regime has been altered through water diversion for agriculture and natural gas extraction and there has been limited study of fish assemblage structure. We analyzed fish data collected from the mainstem Powder River in Wyoming between 1896 and 2008. Shifts in presence/absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
(71 reference statements)
1
5
0
Order By: Relevance
“…Our study supported the notion that trajectories of fish communities in large, altered rivers often are directional and more extreme (Whitten and Gibson-Reinemer 2018) compared with those of fish communities that are composed primarily of native species in smaller and less-altered stream systems (e.g., Matthews et al 2013). Hydrologic variability has been found to a critical component in structuring fish community composition in small and large rivers (Gido et al 2010;Kiernan and Moyle 2012;Senecal et al 2015). Fluctuating water levels in Lake Mohave have been shown to strand and desiccate Razorback Sucker eggs (Minckley and Gustafson 1982), but predation by introduced piscivores has been identified as the main reason for the decline of native fishes in the lower Colorado River (Marsh et al 2015).…”
Section: Speciessupporting
confidence: 83%
See 2 more Smart Citations
“…Our study supported the notion that trajectories of fish communities in large, altered rivers often are directional and more extreme (Whitten and Gibson-Reinemer 2018) compared with those of fish communities that are composed primarily of native species in smaller and less-altered stream systems (e.g., Matthews et al 2013). Hydrologic variability has been found to a critical component in structuring fish community composition in small and large rivers (Gido et al 2010;Kiernan and Moyle 2012;Senecal et al 2015). Fluctuating water levels in Lake Mohave have been shown to strand and desiccate Razorback Sucker eggs (Minckley and Gustafson 1982), but predation by introduced piscivores has been identified as the main reason for the decline of native fishes in the lower Colorado River (Marsh et al 2015).…”
Section: Speciessupporting
confidence: 83%
“…Hydrologic variability has been found to be a critical component in structuring fish community composition in small and large rivers (Gido et al 2010; Kiernan and Moyle 2012; Senecal et al 2015). Fluctuating water levels in Lake Mohave have been shown to strand and desiccate Razorback Sucker eggs (Minckley and Gustafson 1982), but predation by introduced piscivores has been identified as the main reason for the decline of native fishes in the lower Colorado River (Marsh et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We expand on the work of Buckwalter et al (2018) by analysing local (stream segment) and basin-wide (landscape) trends in native and non-native fish abundance, thereby describing a related but distinct aspect of species spread and decline. Studies providing information on both landscape-and population-level aspects of spread and decline of most resident species in a given drainage are relatively rare, despite the fact that both analyses may be important for understanding the conservation status of native species, overall changes in regional fish assemblages, and the potential for impacts of nonnative species (Lyons et al, 1998;Senecal et al, 2015). During successful invasions, non-natives usually undergo predictable periods of establishment within the initial area of introduction, signified by increases in local abundance, followed by geographic spread to nearby locations; research suggests that different characteristics of invaders may be favourable during each of these invasion phases (Marchetti et al, 2004).…”
Section: F I G U R Ementioning
confidence: 99%
“…For Sturgeon Chub, the Powder River (a tributary to the Yellowstone River) historically serves as a stronghold for the species (Stewart 1981;Werdon 1992;USFWS 1993a), with this tributary delineated as a range-wide Sturgeon Chub refuge (Hoagstrom et al 2011). Senecal et al (2015) identified a substantial decrease in Sturgeon Chubs in the Powder River since 1980, with the species noted as rare by 2008. By contrast, Stagliano (2014) indicated that Sturgeon Chubs in the Powder River rebounded from low collection frequencies during 2005-2011 (present at 13% of sites) to increased occurrence during 2012-2013 (present at 65% of sites).…”
Section: Introductionmentioning
confidence: 99%